Funcionalidade do assoalho pélvico de idosas ativas fisicamente com e sem incontinência urinária de acordo com estrato etário - Cielo, Adriana (2018)
Studies show that urinary incontinence (UI) is associated with pelvic floor function, but little is known about this relationship in physically active elderly women according to the age stratum. The objective of this study was to analyze the functionality of the pelvic floor of physically active elderly women with and without urinary incontinence, according to the age stratum. This is a comparative descriptive research. The participants of the study were 79 elderly, 60 to 77 years old, with preserved cognitive function (Mini Mental State Examination), with functional independence (Katz Scale) and active physically evaluated by the accelerometer, enrolled in a university extension program and unit of the municipality of Santa Maria, RS. As a research instrument, the diagnostic data sheet with identification data, sociodemographic characteristics, urogynecologic aspects, health conditions such as presence of UI and physical activity, and functional evaluation of the pelvic floor were performed using the PERFECT Scheme. This research was approved by the Research Ethics Committee of the Federal University of Santa Maria. After the invitation, through direct contact with the participants in the places where they participate in activities of the third age, the collection of data was scheduled. In this, the instruments were applied individually in the form of interviews, in adequate physical space and by previously trained researchers. The accelerometer was used seven days a week, with prior guidance for use. In order to compare the pelvic floor and its components (strength, resistance, repetition and rapidity) with the elderly women with and without UI, the t-test was used for independent samples or Mann Whitney U test (continuous variables), according to data distribution, or on Thu Fisher Square or Exact (categorical variables). The level of significance was 5%. The study included 79 physically active elderly women, 40 with UI and 39 without UI. The elderly practiced a higher weekly percentage of light physical activities. As to the functionality of the pelvic floor, the elderly of both groups presented a median strength of 2 to 3, maintenance of 0 to 2 seconds and of 2 to 3 repetitions of contractions maintained, differing in the number of fast contractions, where the group with IU presented from 3 to 4 and the group without UI 5 or more, only differing significantly when comparing groups with and without UI of different age groups, where the older women who had UI had a lower number of repetitions maintained compared to those had no urine leakage. It was concluded that there was no significant difference in the functionality of the pelvic floor of the elderly in general, but that aging proved to be a strong factor influencing the genesis of UI, since only the older women with UI had a lower number of repetitions than the other elderly women.